(3GdEKfG YTQjIs - (3GdYGedj, GdMGQKj, GdgePGfj, HgGA GdOjf, eMeO Hf MSjf Hf YHO GdUeO, J (B1031(3g`s ((3eMeO Hf eMeO GdLRGFQjs)
(3ChdgG (B:s
(3GdMeO ddg Ydi BdGFg(B... (3hHYO ajbhd(B... (3HgGA GdOHf GdYGedj(B... (3gPg QSGdI GKfi YTQjI JJdh Ydjc efGSc ML GdJeJY Ydi fgL bQjH GKJfi YTQj hCSdhH ZQjH YHbQj(B...s
(3BNQgG (B:s
(3GdMGOj YTQ(B: (3Cf JMSjf GdNdb ajg LhGR Ydi GdUQGW jhe JRd ajg GdCbOGe(B... (3cKhGH NJe GdbQBf aj ZjQg(B. (3JeJ GdQSGdIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B6(3, U(B102s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B251s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B251s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis